Iraq Crude Oil Exports – July, August, September/ 2019 - SOMO, Ministry of oil - oil marketing company (Journal of Petroleum Research and Studies, 2021)
Table 1. Iraq Crude Oil Exports – July 2019 Table 2. Iraq Crude Oil Exports – August 2019 Table 3. Iraq Crude Oil Exports – September 2019